SINERGITAS KUALITAS PRODUK BUAH-BUAHAN TERHADAP MINAT PEMBELIAN KEMBALI KONSUMEN DI TOKO BERKAH BUAH PADALARANG - Hadi, Rusman; Solihin, Dadin (Jurnal Pelita Nusa, 2024)
Repeat purchase interest occurs after a consumer makes a transaction and is influenced by various factors, such as promotion, satisfaction, service quality, and product quality. This study aims to analyze the influence of product quality on consumer repurchase interest at the Padalarang Fruit Blessing Shop, West Bandung. The research used a quantitative approach with a survey method, involving 100 respondents through a saturated sample technique. The results of the study show that product quality and consumer repurchase interest are in a very strong category. The linear relationship between product quality (X) and repurchase interest (Y) has a correlation coefficient of 0.52, with product quality able to explain 27.1% of the variation in repurchase interest, while the remaining 72.9% is influenced by other factors. The influence test showed a t_hitung value of 6.034, greater than t_tabel 0.67703, and a p-value below 0.000. Every one-point improvement in product quality can increase repurchase interest by 0.484 points. This emphasizes the importance of maintaining product quality to increase consumer loyalty and provide added value for the Padalarang Fruit Blessing Shop.